Pengaruh Kualitas Produk dan Gaya Hidup Terhadap Keputusan Pembelian Sepeda Motor Kawasaki Di Kota Tangerang - Umban Adi Jaya; Ira Astira (Cakrawala Repositori IMWI, 2021)
This study aims to determine the effect of product quality and lifestyle on purchasing decisions for Kawasaki motorcycles. The research process is deductive in nature, where to answer the problem formulation, concepts or theories are used so that hypotheses can be formulated. The hypothesis is then tested through field data collection using a questionnaire distributed to 100 samples with purposive sampling technique that has criteria as a Kawasaki motorcycle user in Tangerang City. The results of this study indicate that: (1) Product quality has a positive and significant effect on purchasing decisions, as evidenced by the t-count value of 6.599 and the regression coefficient having a positive value of 0.288; (2) Lifestyle has a positive and significant effect on purchasing decisions, as evidenced by the t-count value of 2.641 and the regression coefficient has a positive value of 0.287; and (3) product quality and lifestyle have a positive and significant effect on purchasing decisions as evidenced by the F count result of 42,902 with a significance of 0.000. (4) The magnitude of the influence of product quality and lifestyle on purchasing decisions is evidenced by the adjusted R square value of 0.611 indicating that the ability of the independent variable to explain the variation of the dependent variable is 61.1% and the remaining 38.9% is explained by other variables outside this research model